2008
DOI: 10.1016/j.bbamem.2008.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Roles of membrane structure and phase transition on the hyperosmotic stress survival of Geobacter sulfurreducens

Abstract: Geobacter sulfurreducens is a delta-proteobacterium bacteria that has biotechnological applications in bioremediation and as biofuel cells. Development of these applications requires stabilization and preservation of the bacteria in thin porous coatings on electrode surfaces and in flow-through bioreactors. During the manufacturing of these coatings the bacteria are exposed to hyperosmotic stresses due to dehydration and the presence of carbohydrates in the medium. In this study we focused on quantifying the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Several studies have shown that decreasing the rate of perturbation improves cell survival after extreme dehydration. This kinetic effect was observed during dehydrations performed according to drying [22] or hyperosmotic treatments [13,23]. These results suggest that the structural evolution of the membrane depends on the kinetics of applying a strongly dehydrating medium to the cells.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Several studies have shown that decreasing the rate of perturbation improves cell survival after extreme dehydration. This kinetic effect was observed during dehydrations performed according to drying [22] or hyperosmotic treatments [13,23]. These results suggest that the structural evolution of the membrane depends on the kinetics of applying a strongly dehydrating medium to the cells.…”
Section: Introductionmentioning
confidence: 68%
“…This event increases the cell surface-to-volume ratio (s/v), causing plasma membrane deformations such as ruffles, wrinkles, and surface roughness [9,10]. The fluidity and structural arrangement of membrane lipids also change; for example, their mobility decreases and the transition from the liquid lamellar to gel or hexagonal phases can occur under conditions of low water content [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…a solid ordered phase. This gel lipid phase is not commonly found in living cells, especially eukaryotic cells, under physiological conditions (27)(28)(29)(30). Although the amplitude of this lifetime component was small (Fig.…”
Section: Plasma Membrane Of S Cerevisiae Contains Highly Orderedmentioning
confidence: 99%
“…Another study based on FTIR (Fourier-transform infrared spectroscopy), also using live A. laidlawii bacteria, showed that, at 30°C (i.e., the growth temperature), a significant percentage of lipids was in the gel phase, and that below 20°C, the membranes were entirely in gel phase, whilst very high viability was still preserved (98–99%; Cameron et al, 1983). A recent study also based on FTIR has shown that, in Geobacter sulfurreducens, gel phases are caused by osmotic stress or desiccation (Ragoonanan et al, 2008). Although the above studies, which are mostly based on “forced-feeding” saturated fatty acids are not entirely physiological, they do show that bacterial cells can survive and even grow containing high amounts of gel phase in their PM.…”
Section: Microdomains In Bacterial Membranesmentioning
confidence: 99%